1997
DOI: 10.1007/s005200050056
|View full text |Cite
|
Sign up to set email alerts
|

Changes in self-concept and body image during alopecia induced cancer chemotherapy

Abstract: Alopecia as a result of cancer chemotherapy has been reported to cause changes to the self-concept and body image. In a prospective longitudinal study, self-concept and body image were analysed in 29 patients after histological confirmation of gynaecological malignancy, mainly ovarian cancer, who were assigned to receive a complete-alopecia-inducing PEC combination chemotherapy (cisplatin 50 mg/m2, epirubicin 60 mg/m2, and cyclophosphamide 500 mg/m2 in 1 day every 28 days). The analysis was performed before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
65
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 0 publications
1
65
0
Order By: Relevance
“…Therefore, despite their reductive nature, these in vitro models have provided experimental evidence for the clinically-reported cytoprotective role of cooling and represent useful tools for future studies on the molecular mechanisms of cooling-mediated cytoprotection. Chemotherapy-induced alopecia (CIA) is the most common and distressing side effect of anticancer chemotherapy (Wang et al, 2006) and the anxiety caused by the prospect of CIA can cause patients to even refuse treatment in certain cases (Munstedt et al, 1997). Thus development of an effective CIA preventative regime represents an important challenge in oncology (Paus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, despite their reductive nature, these in vitro models have provided experimental evidence for the clinically-reported cytoprotective role of cooling and represent useful tools for future studies on the molecular mechanisms of cooling-mediated cytoprotection. Chemotherapy-induced alopecia (CIA) is the most common and distressing side effect of anticancer chemotherapy (Wang et al, 2006) and the anxiety caused by the prospect of CIA can cause patients to even refuse treatment in certain cases (Munstedt et al, 1997). Thus development of an effective CIA preventative regime represents an important challenge in oncology (Paus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological effects of alopecia are understudied but it is one of the prime concerns among patients receiving chemotherapy especially women. 12,13 In one study, 8% women were found to be at risk of avoiding treatment secondary to fear of baldness. 14 Irreversible/permanent alopecia has been described but its exact incidence remains unknown 4-9 and its mechanism is not well studied.…”
Section: Discussionmentioning
confidence: 99%
“…Hair loss is also a traumatic experience and can impose detrimental and long-lasting impacts on body image, sexuality and self-concept (Batchelor, 2001;Münstedt et al, 1997). In fact, women with breast cancer often consider scalp hair loss as the most distressing appearance-altering side effect of chemotherapy treatment, followed by the loss of eyebrows and loss of eyelashes (Nozawa et al, 2013).…”
Section: What Is the Impact Of An Altered Appearance For Women With Bmentioning
confidence: 99%
“…In fact, women with breast cancer often consider scalp hair loss as the most distressing appearance-altering side effect of chemotherapy treatment, followed by the loss of eyebrows and loss of eyelashes (Nozawa et al, 2013). One study found that body satisfaction which dropped during treatment, failed to improve to pre-treatment levels when the hair started to grow back (Münstedt et al, 1997). The loss of hair is often experienced more negatively than the loss of a breast, with hair considered integral in the sense of identity and its loss representing a visible reminder of the cancer, leaving the person to feel like a "cancer patient" (Browall et al, 2006;Freedman, 1994).…”
Section: What Is the Impact Of An Altered Appearance For Women With Bmentioning
confidence: 99%